Does Premedication with Mucolytic Agents Improve Mucosal Visualization during Oesophagogastroduodenoscopy: A Systematic Review and Meta-Analysis. (22nd January 2021) - Burke, Eoghan; Harkins, Patricia; Moriarty, Frank; Ahmed, Ibrahim
Abstract : Introduction . Gastric Cancer (GC) is the fourth most common malignancy worldwide and the second leading cause of cancer-related mortality for both sexes. The gold standard for diagnosing GC is oesophagogastroduodenoscopy (OGD). Excess mucus on the gastric mucosa impairs the detection of early GC. Aim . To synthesize available evidence of the effect of premedication with a mucolytic agent among adults undergoing elective nontherapeutic OGD, compared to placebo or other mucolytic agents, on mucosal visibility during OGD. Methods . A systematic review was conducted. PubMed, EMBASE, CINAHL, Cochrane central register of controlled trials (CENTRAL), and Web of Science were searched for relevant studies. A random-effects meta-analysis was performed to determine the mean difference in total mucosal visibility score (TMVS) between the pooled mucolytic agents and control. Subgroup analyses were performed to determine the mean TMVS difference for simethicone versus control and the impact of different timings and doses of mucolytic premedication. Results . 13 studies, involving 11, 086 patients, including 6178 females (55.7%), with a mean age of 53.4 were identified and 6 of these were brought forward to meta-analysis. This revealed a mean difference of −2.69 (95% CI −3.5, −1.88) in total mucosal visibility scores (TMVS) between the pooled mucolytic agents and control. For simethicone, the mean difference was −2.68 (95% CI −4.94, −0.43). A simethicone dose of 133 mg was most effective with a mean difference of −4.22 (95% CI −5.11, −3.33). Assessing timing of administration across all mucolytic agents revealed a mean difference for the >20 minutes group of −3.68 (95% CI −4.77, −2.59). No adverse events were reported in any included trials. Conclusions . Regular use of premedication with mucolytic agents prior to routine OGD is associated with improved TMVS with no reported adverse events.